Guidance and Counseling Management on Personal, Social, Learning and Career Development of SMK 19 Bandung Students During Covid-19 Pandemics - Alfaris, Muhammad Muadz; Sauri, Supyan; Gaffar, M Andriana (Journal of Social Work and Science Education, 2021)
Education in schools does not only teach subjects but is also given guidance and counseling. Guidance and counseling is a service to students individually or in groups to be able to be independent and develop optimally in personal, social, learning, and career aspects. During the Covid-19 pandemic, learning activities were carried out online or called Learning From Home (LFH). This study explored guidance and counseling management on the personal, social, learning, and career development of SMKN 9 Bandung students during the Covid-19 pandemics. This study used a descriptive method through a qualitative approach. Based on the results, (1) at the planning stage, the school counselor completed the needs assessment, processed, and identified the results. In addition, the school counselor planned the guidance and counseling planning containing the objectives; methods, tools, media; procedures, and evaluation, (2) at the implementation stage, the school counselor has provided services in accordance with the guidance and counseling planning prepared previously, (3) at the evaluation stage, the school counselor completed evaluation on the service results, (4) the constraints or problems faced were students are bored with distance learning, lack of parental guidance and assistance when studying at home, and lack of understanding on IT (internet), (5) as an effort to overcome constraints, the school counselor motivates students to continue to be enthusiastic about learning through online learning materials, instructing parents to pay attention to studying from home, and try as optimally as possible (in these difficult conditions) to provide online services to students.